2016
DOI: 10.1016/j.ijfoodmicro.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces strains producing mitochondriotoxic antimycin A found in cereal grains

Abstract: Reasons for mammalian cell toxicity observed in barley and spring wheat grains were sought. Streptomyces sp. isolates from wheat and barley produced heat-stable methanol-soluble substances which inhibited the motility of exposed porcine spermatozoa used as a toxicity indicator. Several barley isolates produced antimycin A (2 to 5 ng/mg wet wt of biomass), a macrolide antibiotic known to block oxygen utilization in mitochondria. The antimycin-producing isolates were members of the Streptomyces albidoflavus grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Transient receptor potential (TRP) channels in the chemosensory trigeminal C-fibers innervating the nasal cavity, throat, and conjunctiva and in the vagal C-fibers innervating the lower respiratory tract can sense irritating and toxic chemicals [87,88]. The sperm-toxic microbial toxin antimycin A has been shown to cause mitochondrial dysfunction, mtROS production, and C-fiber activation via TRP channels in experimental mice models [89][90][91]. When exposed to mtROS-even non-toxic concentrations of chemicals, LPS, or inflammatory mediatorsthis chemosensory system can induce neurogenic inflammation via neuropeptide secretion and mast cell degranulation [90,[92][93][94][95][96][97][98].…”
Section: Discussionmentioning
confidence: 99%
“…Transient receptor potential (TRP) channels in the chemosensory trigeminal C-fibers innervating the nasal cavity, throat, and conjunctiva and in the vagal C-fibers innervating the lower respiratory tract can sense irritating and toxic chemicals [87,88]. The sperm-toxic microbial toxin antimycin A has been shown to cause mitochondrial dysfunction, mtROS production, and C-fiber activation via TRP channels in experimental mice models [89][90][91]. When exposed to mtROS-even non-toxic concentrations of chemicals, LPS, or inflammatory mediatorsthis chemosensory system can induce neurogenic inflammation via neuropeptide secretion and mast cell degranulation [90,[92][93][94][95][96][97][98].…”
Section: Discussionmentioning
confidence: 99%
“…In the purified components, soil isolates of S. sampsonii can produce heptaene polyene antibiotics [18,27], In addition, S. sampsonii has been shown to produce hydrolytic enzymes, such as amylase, chitinase, protease, and lipase [19]. Studies at the molecular level have focused on strain identification and the phylogenesis of related species [28][29][30][31][32][33][34][35]. The complete genome sequence of Streptomyces sampsonii KJ40 was recently described by our lab [36], resulting in the discovery of a large number of gene encoding chitinases and enzymes involved in secondary metabolite production.…”
mentioning
confidence: 99%
“…Numerous bacteria belonging to Streptomyces genus were recently found on barley and spring wheat grains. The authors also reported the presence of antimycin A toxin‐producing strains in barley, which is the first report of antimycin A in a food substance (Rasimus‐sahari, Mikkola, Andersson, Jestoi, & Salkinoja‐salonen, ).…”
Section: Microbial Challenges Associated With Cereal Grainsmentioning
confidence: 87%